Optical and Spectroscopic Properties of Lorenzenite, Loparite, Perovskite, Titanite, Apatite, Carbonates from the Khibiny, Lovozero, Kovdor, and Afrikanda Alkaline Intrusion of Kola Peninsula (NE Fennoscandia) - Miłosz Huber; Daniel Kamiński; Grzegorz Czernel; Evgeni Kozlov (Crystals, 2022)
This manuscript deals with the analysis of significant rare earth elements (REE) minerals such as eudialyte, lorenzenite, loparite, perovskite, titanite, apatite, and carbonates. These minerals are found in the rocks of the Khibiny, Lovozero, Afrikanda, and Kovdor massifs (the Paleozoic hotspot activity in the Kola-Karelian Alkaline Province is estimated at about 100,000 km2). Performed microscopic analyses that demonstrated their structure and optical features (dimming, interference colors, relief). Single-crystal analysis using XRD methods, SEM-EDS, and spectroscopic (FTIR) studies allowed the characteristics of described minerals: Lorenzenite in Lovozero probably crystalized after loparite have small additions of Nb, La, Ce, Pr, and Nd. Loparite and perovskite have the addition of Ce, Nb, and Ta. The same dopants have titanite probably crystalized after perovskite. Calcite in these massifs had the addition of Ce and Sr, the same as in fluorapatite, which was found in these rocks too. All of the analyzed minerals are REE-bearing and can be considered as deposits.